Diseño de un corredor integral de conectividad para la conservación y valoración de los espacios naturales en la Reserva de Producción Faunística de Chimborazo - Escobar Lata, Mateo Sebastián (2026)
The Chimborazo Wildlife Reserve, one of Ecuador's most important natural attractions and a fundamental part of the National System of Protected Areas, covers an area of 58,560 hectares, with an altitude ranging from 3,800 to 6,310 meters above sea level, with the summit of Chimborazo volcano being the highest point. This vast territory has a rich biodiversity that can be experienced in snowy and biotic ecosystems, bodies of water, forests, trails, caves, as well as geologically interesting places. However, given this situation, the focus and demand have been predominantly on the volcano, which has led to oversaturation and neglect of other areas. The intersection of San Juan and the access to the Reserve is a focal point that links several currently disconnected destinations which, with the provision of responsible landscape intervention, can promote balanced use of resources and positive economic, recreational, and community development. Therefore, the proposal for a tourist corridor emerges as a comprehensive connection strategy to promote accessibility, as well as conservation of the environment and preservation of ecosystems. Similarly, the architectural design of environmentally friendly infrastructures is proposed which, based on a detailed study of the landscape, allows for the establishment of guidelines and approaches for the diversification of uses and improvement of the visitor experience. This is in response to the dialogue between human interaction and the natural environment, ensuring its long-term sustainability and users' empirical appropriation of the environment.